The importance of the government’s internal mechanisms in improving performance (Economic studies journal, 2020)
This study aimed to identify the importance of the internal mechanisms of governance in improving performance of Libyan commercial banks. To achieve the objective of the study, it was designed a survey distributed to the area of the study component of Libyan commercial banks located between the cities of Sirte and Ras Lanuf where a number of questionnaires were handed out to 12 banks. A total of 60 questionnaires were distributed to bank managers and their assistants, internal audit department heads and staff, heads and staff of current account sections and some other staff, of which 54 questionnaires were returned and valid for analysis. The Social Science Statistical Package Program has been used (SPSS) to process the collected data. This is done using descriptive statistics and indicative statistics for data analysis. The study reached several results, the most important of which was the existence of a statistically significant importance, at the level of (a=0.05) of the internal mechanisms of governance (Board of Directors - Internal Audit ) in improving performance of Libyan commercial banks. In addition, the study found that there was no difference between the views of the sample study on the extent of importance of the internal mechanisms of governance in improving performance of Libyan commercial. Based on the findings of the study, the study recommends that the capabilities of the employees of Libyan commercial banks should be strengthened this is done by conducting ongoing training courses for them on how to apply the governance mechanisms, in line with the updates and the latest developments in this field.
Keywords: internal mechanisms of governance, improved performance, commercial banks